2017
DOI: 10.1097/sla.0000000000002398
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia

Abstract: Sarcopenia increases through multimodal therapy, is associated with an increased risk of major postoperative complications, and is prevalent in survivorship. These data highlight a potentially modifiable marker of risk that should be assessed and targeted in modern multimodal care pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(41 citation statements)
references
References 45 publications
5
34
2
Order By: Relevance
“…Although in our study no significant differences in post‐operative complication incidence and severity between patients with and without sarcopenia were seen, another study showed in a cohort of 207 adenocarcinoma patients that sarcopenia was associated with a five‐fold increased risk of major morbidity and a two‐fold increased risk of pulmonary complications . While the sample sizes and treatment of patients in both studies were similar, patients in the present study have a higher American Society of Anaesthesiologists score, and almost double the number of patients had cardiovascular co‐morbidities and/or type 1 diabetes, which might have contributed to the much higher overall incidence of major complications in the present study.…”
Section: Discussioncontrasting
confidence: 72%
“…Although in our study no significant differences in post‐operative complication incidence and severity between patients with and without sarcopenia were seen, another study showed in a cohort of 207 adenocarcinoma patients that sarcopenia was associated with a five‐fold increased risk of major morbidity and a two‐fold increased risk of pulmonary complications . While the sample sizes and treatment of patients in both studies were similar, patients in the present study have a higher American Society of Anaesthesiologists score, and almost double the number of patients had cardiovascular co‐morbidities and/or type 1 diabetes, which might have contributed to the much higher overall incidence of major complications in the present study.…”
Section: Discussioncontrasting
confidence: 72%
“…Although the majority of esophageal cancer patients in Korea are men with squamous cell carcinoma [56], further studies that include women and various histologic types of esophageal cancer are needed. Finally, because there is no definite consensus on the cut-off value of SMI for defining sarcopenia, this study adopted the value proposed by a previous population-based study [27], which was used in several recent studies on cancer patients [57][58][59]. However, future studies are needed to determine the exact cut-off value of SMI for defining sarcopenia considering the characteristics of East Asian individuals.…”
Section: Discussionmentioning
confidence: 99%
“…There is an abundance of data, however, on archived CT scans readily available in oncology clinics globally, which allow retrospective evaluation of quantitative muscle mass, muscle quality, and fat mass. This tactic has spawned a host of studies in all age groups that have demonstrated correlations between skeletal muscle depletion and various outcomes, including increased complications from surgery [54,55], toxicity from chemotherapy [56,57], and, most notably, poorer overall survival [58][59][60]. In older adults with cancer, however, correlations between skeletal muscle depletion alone and adverse outcomes are less clear.…”
Section: Outcomes In Older Adults With Cancer and Wasting Disordersmentioning
confidence: 99%